Biological characteristics of a neolithic human group from Chodzież - Henneberg, Maciej; Kaczmarek, Maria; Szymandera, Wiesława (Anthropological Review, 1982)
The present paper contains morphological and demographic characteristics of a local group of people of Globular Pottery culture based on analysis of skeletal remains excavated from a large common grave at Chodziez (NW Poland) dated approximately at 2500 years B. C. Skeletal remains were irregularly placed, fragmented, mixed giving general impression of a secondary internment. Morphological analysis enabled the authors to distinguish skeletons, or parts thereof, of 30 individuals of both sexes and practically of all ages. Sex ratio among adults was 1.29. Distribution of ages at death was used for construction of a life table (table 2). With specific assumptions concerning fertility parameters of the life table allow to conclude that the group was capable of natural increase (table 3). Applying special methods to mortality data it has been found that in the group opportunity for operation of natural selection was high (Ibs=0.44; Rpot==0.81) similar to that in other prachistoric populations. On grounds of newborn life expectancy, number of individuals buried and assumed time span during which the grave at Chodzież had been used the authors have estimated size of a living group related to the site. Depending on assumed time of usage (25 or 50 yrs.) group size varies from 21 to 42 individuals. Osteometry and craniometry of all possible (due to the state of preservation) remains is presented in the tables. Stature estimated from lengths of long bones is on average 166.6 cms in males and 160.0 cms in females. Six of the adult skulls are preserved well enough for comparative analysis. Applying Penrose's method of biological distance the said six crania were compared separately with means of cranial dimensions of 13 neolithic cranial series from the territory of Europe. These comparisons allow the authors to conclude that the group in question did not differ morphologically from other neolithic groups of Europe. In face of the fact that also paleodemographic analysis did not reveal any peculiarities the group from Chodzież may be accepted as a typical human group of the Globular Pottery Culture — Northern Europe Neolithic pastoralists.